2013
DOI: 10.9755/ejfa.v25i11.16499
|View full text |Cite
|
Sign up to set email alerts
|

Application of mycorrhizae in sustainable date palm cultivation

Abstract: Date palm (Phoenix dactylifera) is a significant and developing crop especially in the Arabian Peninsula, the Middle East and North Africa regions. The area under cultivation of this tree is increasing annually. Date palms usually grown under harsh and unfavorable growing conditions with low rainfall and high rates of evaporation as well as in soils with low organic matter and nutrient deficiencies. Hence, date palm cultivation becomes dependent on application of high levels of fertilizers as well as on irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In exchange for carbohydrates, the fungi provide the associated plant with resources such as phosphate and nitrogen. The presence or absence of AMF is therefore probably key to plant fitness, including in palms (Moora et al ., ; Al‐Karaki, ). Thus, the reduction in AMF in H. forsteriana on volcanic soil may place it at a substantial disadvantage compared with H. belmoreana .…”
Section: Discussionmentioning
confidence: 99%
“…In exchange for carbohydrates, the fungi provide the associated plant with resources such as phosphate and nitrogen. The presence or absence of AMF is therefore probably key to plant fitness, including in palms (Moora et al ., ; Al‐Karaki, ). Thus, the reduction in AMF in H. forsteriana on volcanic soil may place it at a substantial disadvantage compared with H. belmoreana .…”
Section: Discussionmentioning
confidence: 99%
“…However, the results from this study support the idea that AMF improves the growth performance of sago palms. Indeed, growth-improvement of date palm and oil palm by AMF were reported [18,19] and salt and drought tolerance in date palm were confirmed [46,47]. To ensure the relationships between sago palm and AMF, inoculating tests of AMF and the correlation analysis of plant growth performance and AMF community structure in the field is needed in the future.…”
Section: Amf Community Structurementioning
confidence: 99%
“…Recent studies have revealed that the inoculation with AMF improves the growth of the Arecaceae family [18,19]. In the case of the sago palm, Chan et al, (2002) [20] detected AMF belonging to Glomales of the Zygomycetes in tropical peat soil.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the use of pesticides is not economically and environmentally commendable because of the low efficiency of most pesticides in use (Al-Jboory et al, 1999Al-Samarraie et al, 1988;Ba-Angood, 1978;Ba-Angood et al, 2009;Ali et al, 2010). Less toxic materials which are called environmentally friendly pesticides are considered as safe alternative for controlling date palm pests (Al-Karaki, 2013;Ali and Mohammad, 2014;Al-Khawaja, 1999;Hama et al, 2002;Hama and Abdul-Razzak, 2006;Dhoubi et al, 2007;Al-Bahely, 2004;Mohammad et al, 2011Mohammad et al, , 2013Mohammad et al, , 2014Sayed et al, 2001;Lysandrou et al, 2010;Gerling et al, 2006). Other means such as light traps were used as monitoring and control tools against date palm pests especially borers (Khalaf et al, 2010).The best solution lies in the development and implementation of an integrated management program that addresses the entire range of date palm pests.…”
Section: Integrated Pest Managementmentioning
confidence: 99%